A peridynamic model for galvanic corrosion and fracture. (20th September 2021) - Zhao, Jiangming; Jafarzadeh, Siavash; Rahmani, Mohammad; Chen, Ziguang; Kim, Yong-Rak; Bobaru, Florin
Highlights: A new coupled peridynamic (PD) model for combined galvanic corrosion and fracture. A new analytical calibration replaces earlier method based on computing a "trial-solution". Corrosion in two different galvanic couple matches well with experiments. Models based on PDEs require a change in geometry at the interface; the PD model does not. Failure of a galvanic couple subjected to combined corrosion and stress is simulated. Abstract: A coupled peridynamic (PD) corrosion-fracture model is introduced, in which the local corrosion rate is determined by solving the corresponding electrostatic problem. By being able to consider variable distributions of corrosion rates along the anodic surface, the model is particularly useful for simulating galvanic corrosion. A novel analytical calibration for parameters in the corrosion model is provided. The corrosion model is verified in terms of the electric potential, current density, and corrosion depth, and validated against experimental results for AE44 (Mg alloy) – mild steel and AE44 – AA6063 (Al alloy) galvanic couples taken from the literature. The PD results are also compared with those from a COMSOL FEM-based model. It is found that an artificial initial "step-down" in geometry at the galvanic joint is required for the COMSOL model in order to provide reasonable results, but it is not needed in the PD model. A coupled galvanic corrosion-fracture problem accounting for the combined electro-chemical attack and strains induced by mechanical loadings is solved. Graphical abstract: Image, graphical abstract